War and democratic constraint how the public influences foreign policy - Baum, Matthew; Potter, Philip B. K. (Princeton University Press, 2015)
War and Democratic Constraint shows that the key to how a government determines foreign policy rests on the transmission and availability of information. Citizens successfully hold their democratic governments accountable and a distinctive foreign policy emerges when two vital institutions--a diverse and independent political opposition and a robust media--are present to make timely information accessible.Matthew Baum and Philip Potter demonstrate that there must first be a politically potent opposition that can blow the whistle when a leader missteps.